Assessing the impact of sodium intake on kidney function deterioration and proteinuria in the general population: A prospective cohort study - Chan Young Park; Jong Hoon Seok; Seung Yoon Lee; Ji Eun Kim (PLoS ONE, 2025)
Excessive sodium intake is recognized as a potential risk factor for various diseases, including kidney disease. However, limited research has been conducted on the relationship between sodium intake and kidney disease in the general population. This study aimed to explore the association between sodium intake and the risk of kidney disease, utilizing multivariable logistic regression and spline interpolation models. Twelve-year prospective cohort data were analyzed, and participants were categorized based on their sodium intake. Kidney disease was defined by the presence of proteinuria and a reduction in estimated glomerular filtration rate below 60 ml/min/1.73m². In the overall population, sodium intake exceeding 2g/day was not significantly associated with kidney dysfunction (adjusted OR: 0.84, 95% CI: 0.67–1.04, p = 0.113). However, in subgroup analyses, individuals with diabetes who consumed more than 5g/day of sodium had a significantly increased risk of kidney dysfunction (adjusted OR: 3.76, 95% CI: 1.36–10.30, p = 0.01). Across both the general population and subgroup analyses, sodium intake was not significantly associated with proteinuria. These findings suggest that while sodium intake may not have a substantial impact on kidney function in the general population, it may play a critical role in accelerating kidney dysfunction in individuals with comorbidities such as diabetes.